Non-parasitic liver cysts - Bercianos, Carlos; Estrugo, Roberto; Perrone, Luis; Paperán, Juan (Cirugía del Uruguay, 1977)
Five cases of non parasitic livers systs are described. After revising different aspects of this subject and national case-material, the author remarks that dysphagia, a rare symptom, was present in one of the cases; that hepatectomy may become imperative by reason of successive recurrences; that internal derivation solved a case of fistulization; and that cystectomy, if feasible, is the ideal treatment.